Nutritional evaluation of functional biscuits supplemented with Malva nuts(Sterculia Lychnophora - Nguyen Van Toan; Nguyen Ngoc Yen Chi, (International Journal of Scientific Research and Management (IJSRM), 2022)
Malva nut or Sterculia lychnophora is a traditional medicine and is widely found in the Southeast Asia region and China. This traditional medicine is known to have good health effects and can act as a food additive to improve the texture of several food products as well as functional ingredients. In this study, nutritional evaluation of functional biscuits supplemented malva nuts (Sterculia lychnophora) was thoroughly and successfully investigated. Consequently, the crude malva nut powders were extracted by using two different solvents (water and ethanol) and were supplemented into biscuits at the level of 2.5%, 5%, 7,5%, and 10%. The physio-chemical determination and sensory evaluation were carried out to all the developed biscuits. Overall, supplementation of crude malva nut powder into biscuits significantly affects the nutritional values and physical properties of developed biscuits. On the nutritional basis, at the same level of supplementation, biscuits supplemented with water extracted crude malva nut powder showed higher fat content while biscuits made with ethanol extracted ethanol demonstrated higher ash, protein, fiber, and total carbohydrates contents, especially at 10% of supplementation. For the sensorial differences, except the 7.5%, biscuits with 2.5%, 5%, and 10% crude malva nut powders clearly unidentical. The obtained results of this study have indicated that the developed biscuits were not only improved in terms of nutritional value and health benefits, but also had high potential of being accepted by consumers.Keywords: malva nut, Sterculia lychnophora, solvents, functional biscuits